A corpus-based analysis of emotional insecurity and modern masculinity in Anson Seabra’s album lyrics - Kharien Puspa Maharani; Wiwiek Afifah (Linguistics Initiative, 2026)
Traditional norms of masculinity often prevent emotional openness, causing men to internalize vulnerability and suppress emotional expression. This study aims to examine how emotional adjectives in Anson Seabra's A Heart Is a Terrible Thing to Break album reflect emotional insecurity and representations of modern masculinity through language. Employing a qualitative descriptive approach supported by corpus-based analysis, this study identifies the most frequently used adjectives, which are broken, hurt, wrong, and good. Following this, the adjectives are analyzed for their use through semantic and sociolinguistic perspectives based on the context in the lyrics. The findings reveal that these adjectives frequently appear in lyrical contexts that portray self-doubt, emotional fragility, and fear of relationship failure. The results provide insight into the internal conflicts faced by male characters in articulating vulnerability. This research enhances both the fields of linguistics and gender studies by revealing how artistic language in music could challenge traditional concepts of manhood and function as a medium for emotional expression.